ANALISA KINERJA JALAN PENDEKAT PADA BEBERAPA JEMBATAN DI KOTA PALU (Studi kasus: Jembatan Palu I, II, III dan IV) - Patunrangi, Jurair (Jurnal REKAYASA dan MANAJEMEN TRANSPORTASI, 2011)
Bridge approach road of Palu I is the central commercial area that serves as the main road. Thebridge approach road of Palu II is a residential area, shop, offices, schools and other public facilities.Bridge approach road of Palu III is a residential area with commercial activities. While the bridgeapproach roads of Palu IV is an area of residential, commercial, office and other public facilities.Traffic congestion on peak hours occur on the approach road on each bridge. Congestion is causedlosses in terms of time, cost, pollution and noise for road users.The purpose of this research are to know the performance of bridge approach roads of Palu I, II, IIIand IV. The data have been collected by surveys of traffic volume during peak hours. Data of trafficstream include flow and velocities of traffic.The results find that the performance of bridge approach roads Palu II, III and IV for current conditionsand five years forward into the category of C and B. While the bridge approach roads of Palu I haveentered at the level of service F.